The World Book Dictionary (Vol.1) A-K - World Book, Inc. (Rawalpindi, Pakistan Army Education Publishing House, 2001)
An English language dictionary which provides definitions, spellings, and pronunciations to more than 225,000 terms.
Include Garph and Illustration
Keywords: English language